Beskrywing en evaluering van verskillende kategetiese beskouings met die oog op die formulering van basisteorieë vir die kategese - M. J. du P Beukes (HTS Teologiese Studies/Theological Studies, 1994)
Description and evaluation of different catechetical ideas in order to formulate basic theories for catechesis In order to formulate basic theories for catechesis various views are considered and evaluated in this article. The following basic theories are the result of the evaluation: Catechesis is an act of communication founded on baptism in service to the gospel of Jesus Christ. It takes place in the form of instruction, with the aid of curriculum models. It takes place during formal catechesis, but it is indirectly affiliated to other functions of the church. It is directed at children of the covenant, and enlists their co-operation. It is ministered by parents, catechists, and the community of the covenant, presenting the Bible as the word of God.